2006
DOI: 10.1007/s00415-006-0058-6
|View full text |Cite
|
Sign up to set email alerts
|

The Italian multicenter observational study on post–stroke depression (DESTRO)

Abstract: Despite growing information, questions still surround various aspects of post-stroke depression (PSD). The Italian multicenter observational study Destro was designed to help clarify in a large sample the frequency and clinical impact of PSD. A total of 53 centers consecutively admitted 1064 patients with ischemic or hemorrhagic stroke, assessing them periodically in the first 9 months after the event. Patients with depression were followed for two years. Depression was diagnosed on clinical examination, verba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
98
2
8

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(118 citation statements)
references
References 47 publications
10
98
2
8
Order By: Relevance
“…37 A prospective cohort study in Italy showed that most poststroke depression occurred in the first 3 months. Late onset of depression occurred occasionally and tended to be milder, 38 but other studies have not found any difference between late-and early-onset depression in risk factor profiles. 39 Poststroke depression has a significant impact on healthcare utilization 40 and mortality.…”
Section: Discussionmentioning
confidence: 84%
“…37 A prospective cohort study in Italy showed that most poststroke depression occurred in the first 3 months. Late onset of depression occurred occasionally and tended to be milder, 38 but other studies have not found any difference between late-and early-onset depression in risk factor profiles. 39 Poststroke depression has a significant impact on healthcare utilization 40 and mortality.…”
Section: Discussionmentioning
confidence: 84%
“…PSD has been linked to decreased quality of life, increased disability, and increased mortality [4,[17][18][19]. In addition, there is an increase in suicidal ideation and suicide after stroke, especially among those with PSD [20,21].…”
Section: Psd and Psf Impair Recovery And Decrease Quality Of Lifementioning
confidence: 99%
“…[1][2][3][4] Given that there are at least 795,000 ischemic strokes yearly in the U.S., 5 a conservative estimate is that almost 180,000 U.S. stroke survivors develop PSD annually. PSD is associated with worse functional outcomes, quality of life, and increased post-stroke mortality.…”
Section: Introductionmentioning
confidence: 99%